(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To Study the management and outcome of Abdominal tuberculosis. Place and Duration of Study: This study was conducted at Jinnah Hospital & Avicenna Medical College Lahore from Jan’ 2009 to Jul’ 2010. Patients and Methods: A total of 38 patients irrespective of age and gender who were diagnosed to be suffering from abdominal tuberculosis were included in the study. Results: 24 patients, (63.15%) were females thus making the majority, while 14 ( 36.85%) were males. 28 patients out of 38, underwent-major surgical procedure like hemicolectomics, resection of small bowel and end to end anastamosis, stricturoplasty, Ileostomy etc., while 10 patients were treated conservatively. All were put on antituberculous therapy. Conclusion: Abdominal tuberculosis continues to be a major health concern in our country. An early diagnosis may prevent the patient from a major disaster, but as it poses diagnostic problems, it is often diagnosed late, presents late with complication that require major surgical procedures.